2021
DOI: 10.1161/jaha.121.023689
|View full text |Cite
|
Sign up to set email alerts
|

Diameter Reduction Determined Through Carotid Ultrasound Associated With Cardiovascular and All‐Cause Mortality: A Single‐Center Experience of 38 201 Consecutive Patients in Taiwan

Abstract: Background Few studies have evaluated the prognostic significance of diameter‐based carotid sonographic measurements for mortality. We investigated whether a reduction in diameter of different carotid anatomical segments is associated with cardiovascular and all‐cause mortality in a hospital‐based cohort with universal health care. Methods and Results We conducted a retrospective cohort study of 38 201 patients who underwent carotid duple… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 41 publications
0
2
0
Order By: Relevance
“…Atherosclerosis is firmly established as a leading cause of clinical cerebrovascular events ( 1 ), and carotid plaques are feasible and useful markers of cardiovascular risk since they are indicators of the general atherosclerotic burden on the arterial tree ( 5 ). Thus, the burden and characteristics of atherosclerosis in the carotid arteries are associated with the atherosclerosis in other regions, such as the coronary arteries ( 6 ), and the grade of carotid stenosis has proven to be an independent risk factor for cardiovascular and all-cause mortality ( 5 ). Additionally, carotid plaques play an important role in the development of ischemic stroke, not only as a proxy of the atherosclerotic burden, but also due to formation and release of thromboemboli following carotid plaque rupture ( 7 ).…”
Section: Introductionmentioning
confidence: 99%
“…Atherosclerosis is firmly established as a leading cause of clinical cerebrovascular events ( 1 ), and carotid plaques are feasible and useful markers of cardiovascular risk since they are indicators of the general atherosclerotic burden on the arterial tree ( 5 ). Thus, the burden and characteristics of atherosclerosis in the carotid arteries are associated with the atherosclerosis in other regions, such as the coronary arteries ( 6 ), and the grade of carotid stenosis has proven to be an independent risk factor for cardiovascular and all-cause mortality ( 5 ). Additionally, carotid plaques play an important role in the development of ischemic stroke, not only as a proxy of the atherosclerotic burden, but also due to formation and release of thromboemboli following carotid plaque rupture ( 7 ).…”
Section: Introductionmentioning
confidence: 99%
“…However, the association between CCA diameter and CVD mortality was not explored in those studies, leaving the prognostic value of CCA for CVD unclear. Additionally, a retrospective cohort study conducted in Taiwan, China, reported an independent association between reduced CCA diameter and CVD mortality [ 16 ]. This finding contrasts with our results.…”
Section: Discussionmentioning
confidence: 99%